Gestión administrativa para la Asociación de Artesanos " La Victoria " del cantón Pujilí. - Lara Naranjo, Alex Bayardo (2021)
Administrative management under its components and different theories, in most cases respond to the changing challenges presented by companies and institutions. Associativity is a type of organization, which is born from the convocation and the popular union, although its nature is different, it also requires administrative tools that lead to success. The research presented has the general objective: To design an administrative management model for the Association of Craft Producers "La Victoria" of the Pujilí canton. The methodology is framed in a quantitative approach, through the application of the deductive method, the type of research was descriptive-explanatory, with a field design, complemented with documentary research techniques, the studied population was made up of the members of the Association of Artisan Producers "La Victoria" of the Pujilí canton, from whom a representative sample of 97 artisans was extracted, to whom a Likert scale-type survey was applied, and a semi-structured interview, answered by the leading leader, of both instruments Validity was obtained through the expert judgment technique, and the reliability questionnaire under Cronbach's Alpha Coefficient, with a scale of 0.853, within the Very High Reliability level. This allowed obtaining results that were triangulated to make a proposal for the MOGANA Administrative Management Model, with viable components that allow visibility and commercialization in the association, incorporating elements in line with current times.